Women, mobile phones, and M16s: Contemporary New Guinea highlands warfare - Macdonald, Fraser (The Australian journal of anthropology, 2017)
This paper reports upon a series of recent developments in New Guinea highlands warfare. Building upon existing literature highlighting the deep influence of modernity within this context, we draw attention to two particular developments yet to be reported in the literature and which appear to be of special significance. Through an analysis of Aiya warfare, Southern Highlands Province, Papua New Guinea, we document the direct and increasing involvement of women within warfare, as well as the important role played by mobile phones used by warriors to communicate before and during fighting. These two developments are situated in relation to broader shifts currently reshaping Melanesian sociality, namely, the ambivalent and fraught position of women within an emergent PNG society, as well as the rapid diffusion of mobile phone technology throughout the region.